2015
DOI: 10.1016/j.jtbi.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Sit-and-wait versus active-search hunting: A behavioral ecological model of optimal search mode

Abstract: We model the behavioral ecology of search mode for randomly moving predator and prey. Active-search is favored at low prey movement velocity, ambush at high prey velocity. Sit-and-wait mode is favored if predator movement is energetically costly. Ambush is favored if faster predator velocity alerts prey or impedes their detection. Optimal predator velocity in active-search mode balances costs against prey movement. a r t i c l e i n f o b s t r a c tDrawing on Skellam's (1958) work on sampling animal populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 65 publications
(64 reference statements)
2
18
0
2
Order By: Relevance
“…In addition, encounter rates of the sit‐and‐wait predator were strongly affected by prey body speed, whereas encounter rates of the active predator were affected by predator and prey body speed. Our results support previous observations and theory predicting that active predators will gain a relative performance advantage when prey speed and density are low, and that sit‐and‐wait strategies will be advantageous when prey speed and density are high (Huey and Pianka 1981, Werner and Anholt 1993, Ross and Winterhalder 2015). In addition, we found that the sit‐and‐wait predator was more energetically efficient, because it had higher growth rates despite lower feeding rates (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, encounter rates of the sit‐and‐wait predator were strongly affected by prey body speed, whereas encounter rates of the active predator were affected by predator and prey body speed. Our results support previous observations and theory predicting that active predators will gain a relative performance advantage when prey speed and density are low, and that sit‐and‐wait strategies will be advantageous when prey speed and density are high (Huey and Pianka 1981, Werner and Anholt 1993, Ross and Winterhalder 2015). In addition, we found that the sit‐and‐wait predator was more energetically efficient, because it had higher growth rates despite lower feeding rates (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with optimal foraging theory, which predicts that, when feeding a predator will maximize its energy intake and minimize its energy expenditure (Godin & Keenleyside, 1984). The ambush mode of foraging is regarded by Ross & Winterhalder (2015) as optimal for fish species, such as O. dentex, that target mobile prey. As O. dentex is a top predator and relatively abundant on the rocky reefs of south-western Australia, it presumably plays an important role in the ecology of that environment.…”
Section: H a R Ac T E R I S T I C S C O N T R I B U T I N G T O S Usupporting
confidence: 81%
“…This is consistent with optimal foraging theory, which predicts that, when feeding a predator will maximize its energy intake and minimize its energy expenditure (Godin & Keenleyside, ). The ambush mode of foraging is regarded by Ross & Winterhalder () as optimal for fish species, such as O . dentex , that target mobile prey.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in prey density (seal numbers) and habitat complexity (kelp density) may explain seasonal changes in fine‐scale behaviour (although we lacked the sample size to test for seasonal effects). Recent theoretical models predict that active searching becomes more advantageous as prey move slower and/or the energetic cost of predator movements decrease (Higginson & Ruxton ; Ross & Winterhalder ). Individuals switching hunting modes may be a strategy in itself, and match the predictions of the game theoretic Ambush Search strategy, where a predator alternates ambush with active searching which is predicted to increase the success of systematic searching (Alpern et al .…”
Section: Discussionmentioning
confidence: 99%